TLR recognition of self nucleic acids hampers glucocorticoid activity in lupus - Guiducci, Cristiana (2010)
Glucocorticoids are widely used to treat patients with autoimmune diseases such as systemic lupus erythematosus (SLE)1,2. However, regimens used to treat many such conditions cannot maintain disease control in the majority of SLE patients and more aggressive approaches such as high-dose methylprednisolone pulse therapy are used to provide transient reductions in disease activity3,4. The primary anti-inflammatory mechanism of glucocorticoids is thought to be NF-κB inhibition5. Recognition of self nucleic acids by toll-like receptors TLR7 and TLR9 on B cells and plasmacytoid dendritic cells (PDCs) is an important step in the pathogenesis of SLE6, promoting anti-nuclear antibodies and the production of type I interferon (IFN), both correlated with the severity of disease1,7. Following their activation by self-nucleic acid-associated immune complexes, PDCs migrate to the tissues8,9. We demonstrate, in vitro and in vivo, that stimulation of PDCs through TLR7 and 9 can account for the reduced activity of glucocorticoids to inhibit the IFN pathway in SLE patients and in two lupus-prone mouse strains. The triggering of PDCs through TLR7 and 9 by nucleic acid-containing immune complexes or by synthetic ligands activates the NF-κB pathway essential for PDC survival. Glucocorticoids do not affect NF-κB activation in PDCs, preventing glucocorticoid induction of PDC death and the consequent reduction of systemic IFN-α levels. These findings unveil a new role for self nucleic acid recognition by TLRs and indicate that inhibitors of TLR7 and 9 signalling could prove to be effective corticosteroid-sparing drugs.